Schwann cells in the normal and pathological lung microenvironment - Shurin, Michael R.; Wheeler, Sarah E.; Shurin, Galina V.; Zhong, Hua; Zhou, Yan (Frontiers in Molecular Biosciences, 2024)
The lungs are a key organ in the respiratory system. They are regulated by a complex network of nerves that control their development, structure, function, and response to various pathological stimuli. Accumulating evidence suggests the involvement of a neural mechanism in different pathophysiological conditions in the lungs and the development and progression of common respiratory diseases. Lung diseases are the chief source of death globally. For instance, lung cancer is the second most commonly diagnosed malignancy, after prostate cancer in men and breast cancer in women, and is the most lethal cancer worldwide. However, although airway nerves are accepted as a mechanistically and therapeutically important feature that demands appropriate emphasizing in the context of many respiratory diseases, significantly less is known about the role of the neuroglial cells in lung physiology and pathophysiology, including lung cancer. New data have uncovered some cellular and molecular mechanisms of how Schwann cells, as fundamental components of the peripheral nervous system, may regulate lung cancer cells' survival, spreading, and invasiveness in vitro and in vivo. Schwann cells control the formation and maintenance of the lung cancer microenvironment and support metastasis formation. It was also reported that the number of lung cancer-associated Schwann cells correlates with patients' survival. Different factors secreted by Schwann cells, including microRNA, are known to sharpen the lung cancer environment by regulating the tumor-neuroimmune axis. Further clinical and experimental studies are required to elucidate the detailed role of Schwann cells in creating and maintaining pulmonary tumor-neuro-immune axis, which will advance our understanding of the pathogenesis of lung cancer and may inform therapeutic hypotheses aiming neoplasms and metastases in the lung.